The consumer behavior in the context of counterfeit products: A bibliometric analysis - Jadach, Robert; Łopatka, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article aims to identify the main areas of works devoted to the topic of counterfeit goods/brands consumption and to present the dynamics of changes in researchers’ interest in this subject. The research method used in the article was bibliometric analysis, complemented by content analysis of literature selected from the Scopus database. Research results: The main areas of research on the issue of counterfeit product consumption focused on 1) online consumer behavior and ethical aspects, 2) consumption of counterfeit products and brands, and 3) social aspects of consumption of counterfeit products. The earliest publications focus on purchasing behavior in the context of buying counterfeit products, followed by researchers who have focused on the ethical aspects of consuming counterfeit goods. More recent studies focus on the consumption and trade of counterfeit goods on the Internet. Conclusions: The ever-expanding global trade in counterfeit products poses a major challenge — it erodes business revenue, undermines innovation, and hampers economic growth. To effectively mitigate these phenomena, it is essential to have up-to-date knowledge of the latest scientific advances in the field. Research into the buyer behavior in the context of counterfeit goods can provide useful information for manufacturers about the scale of the problem and the possible need for remedial action.
Keywords: counterfeit products; fake products; consumer behavior; buyer behavior